Non-Violent Resistance in Nazar’s Comics: A Verbo-Visual Discourse Analysis - Aslam, Sehrish; Janjua, Fauzia (Pakistan Languages and Humanities Review, 2023)
The present study employs a Verbo-Visual Discourse Analysis to comprehensively examine the relationship between comics, women’s empowerment, and nonviolent resistance in the Pakistani context. Focused on Nigar Nazar’s Gogi character, the analysis utilizes visual grammar theory proposed by Kress and Van Leeuwen and Halliday’s SFL. It aims to explore the fusion of verbal and visual elements in Gogi comics, emphasizing their impact on female readers’ perceptions and behaviors. Besides, this research scrutinizes Gogi’s persona, assessing its influence on women’s empowerment and its subversion of social mores, encouraging women to participate in nonviolent resistance activities. The long-term effects of Gogi’s persona on reader engagement in nonviolent activities are also explored. Additionally, the study investigates women readers’ responses to Gogi’s lighthearted approach to empowerment, highlighting the role of humor as an effective medium for conveying messages about nonviolent resistance. The Verbo-Visual Discourse Analysis aims to decipher the semiotic nuances of Gogi comics, emphasizing visual and linguistic components that contribute to shaping the discourse of nonviolent resistance. Through this methodology, the study seeks to advance knowledge and understanding of the transformative potential of comics in challenging societal norms and fostering active engagement in social and political change within the Pakistani setting. Future research could delve into the broader cultural impact of Gogi comics in Pakistan, examining how they contribute to shaping societal perceptions beyond the scope of women’s empowerment and nonviolent resistance. This exploration could shed light on the multifaceted influence of comics on cultural norms and values.